The cooperation between AMI and Brazil: situations and urgencies - Martins, Marco António Baptista; Libório, Tá‚nia Sofia (Revista Brasileira de Ciência Política, 2018)
In a global era, where richness and poverty interact, shining through their potentials and vulnerabilities, the conviction to face that diversity emerges through cooperation in behalf of the sustainable development. The Non-Governmental Organizations (NGOs) have a promoting role to support the development, insofar International Medical Assistance (AMI) acts and cooperates in local and in community development, leading the county’s improvement.